Automated Nerve Monitoring in Shoulder Arthroplasty: A Prospective Randomized Controlled Study. (30th April 2021) - Chui, Jason; Chohan, Moaz B. Y.; Murkin, John M.; Rachinsky, Maxim; Dhir, Shalini; Athwal, George S.; Faber, Kenneth J.; Drosdowech, Darren
Abstract : Background: Evoked potential monitoring is believed to prevent neurologic injury in various surgical settings; however, its clinical effect has not been scrutinized. It was hypothesized that an automated nerve monitor can minimize intraoperative nerve injury and thereby improve clinical outcomes in patients undergoing shoulder arthroplasty. Methods: A prospective, blinded, parallel group, superiority design, single-center, randomized controlled study was conducted. Study participants were equally randomized into either the automated nerve-monitored or the blinded monitored groups. The primary outcome was intraoperative nerve injury burden as assessed by the cumulative duration of nerve alerts. Secondary outcomes were neurologic deficits and functional scores of the operative arm, and the quality of life index (Euro Quality of life-5 domain-5 level score) at postoperative weeks 2, 6, and 12. Results: From September 2018 to July 2019, 213 patients were screened, of whom 200 were randomized. There was no statistically significant difference in the duration of nerve alerts between the automated nerve-monitored and control groups (median [25th, 75th interquartile range]: 1 [0, 18] and 5 [0, 26.5]; Hodges–Lehman difference [95% CI]: 0 [0 to 1] min; P = 0.526). There were no statistically significant differences in secondary outcomes between groups. However, in the ancillary analysis, there were reductions in neurologic deficits and improvements in quality of life index occurring in both groups over the course of the study period. Conclusions: Protection from nerve injury is a shared responsibility between surgeons and anesthesiologists. Although a progressive improvement of clinical outcomes were observed over the course of the study in both groups as a consequence of the real-time feedback provided by the automated nerve monitor, this trial did not demonstrate that automated nerve monitoring by itself changes important clinical outcomes compared with no monitoring. Abstract : Using a prospective study design, automated nerve monitoring with feedback versus blinded monitoring during shoulder arthroplasty was not associated with a reduced duration of nerve alerts. Secondary outcomes such as neurologic deficits and quality of life indices did not differ between the groups, although these outcomes improved in both groups over the course of the study. Supplemental Digital Content is available in the text.